Added tax: the legal practice of the European Court of Justice securing value - Alexandru ARMEANIC (ACROSS)
One of the most complex and important sources of the European fiscal legal framework is the activity of the European Court of Justice regarding the interpretation and application of directives. The judicial practice developed by the Court contains dozens of tax disputes, which include cases of violation and incorrect understanding of the provisions of the Value Added Tax (VAT) directives. Therefore, the Decisions of the European Court, related to the application of directives, represent themselves a stage of legislative creation, upon completion of which the directive becomes practically applicable. From the mentioned European judicial practice, we can conclude that the European Court of Justice has a special influence on the application of the rules of European law. The Court's rulings favored the development of European fiscal rules by interpreting directives and establishing prohibitions on actions that do not correspond to the principles of European law and the securing of European fiscal revenues. Finally, the elaboration of the directives, as a legal form of harmonization of the legal framework, as a principle and method of unification of the fiscal legislation of the member states, created sufficient legal conditions for solving the problems in the scope of the European fiscal policy and securing these revenues of the Union European.